Effect of atrial fibrillation on outcomes after mechanical thrombectomy and long-term ischemic recurrence in patients with acute basilar artery occlusion - Zhao, Chenhao; Luo, Weidong; Liu, Xing; Luo, Jun; Song, Jiaxing; Yuan, Junjie; Liu, Shuai; Huang, Jiacheng; Kong, Weilin; Hu, Jinrong; Yang, Jie; Sun, Ruidi; et al. (Frontiers in Neurology, 2022)
IIntroduction 45 According to literature on anterior circulation, comorbid atrial fibrillation (AF) is not 46 associated with a worse functional outcome, lower reperfusion rates, or higher rates of 47 intracranial hemorrhage after mechanical thrombectomy (MT) compared to intravenous 48 thrombolysis (IVT) or treatment with supportive care. However, data are limited for the 49 effect of comorbid AF on procedural and clinical outcomes of acute basilar artery 50 occlusion (ABAO) after MT. This study aimed to investigate the effect of atrial 51 fibrillation on outcomes after MT and long-term ischemic recurrence in patients with 52 ABAO. 53 Methods 54 We performed a register study of the Endovascular Treatment for Acute Basilar Artery 55 Occlusion Study (BASILAR, which is registered on the Chinese 56 Clinical Trial Registry，http://www.chictr.org.cn;ChiCTR1800014759) from January 57 2014 to May 2019 and included 647 patients who underwent MT for ABAO, 136 of 58 whom had comorbid AF. Prospectively defined baseline characteristics, procedural 59 outcomes, and clinical outcomes were reported and compared. 60 Results 61 On multivariate analysis, AF predicted a shorter puncture-to-recanalization time, higher 62 first-pass effect rate, and lower incidence of angioplasty and/or stenting (p<0.01). AF 63 had no effect on intracranial hemorrhage incidence (adjusted odds ratio [aOR], 1.093; 64 95% confidence interval [CI], 0.451–2.652), 90-day functional outcomes (adjusted 65 common odds ratio, 0.915; 95% CI, 0.588–1.424), or mortality (aOR, 0.851; 95% CI, 66 0.491–1.475) after MT. The main findings were robust in the subgroup and 1-year 67 follow-up analyses. Comorbid AF was the remaining predictor of ischemic recurrence 68 (aOR, 4.076; 95% CI, 1.137–14.612). 69 Conclusions 70 The study revealed no significant difference in the safety and efficacy of MT for ABAO 71 regardless of whether patients had comorbid AF. However, a higher proportion of 72 patients with AF experienced ischemic recurrence within 1 year after MT.